Time in social media applications: a definition and a tool to analyse technological affordances of time - Palomar-Garcia, Clara; Fernandez-Planells, Ariadna; Sora-Domenjó, Carles (Frontiers in Communication, 2025)
Digital temporalities have been studied in depth from the point of view of how a user perceives them. However, a systematic analysis of how social media apps generate certain temporal experiences is still needed. The purpose of this paper is to analyse how social media applications structure the experience of time. To do so, we first propose a set of characteristics relating to time in digital media based on the literature; second, we design and validate a new system of analysis that allows the evaluation of the technological affordances of time in social media applications. The tool has been validated on a test sample of four social media apps (Facebook, Instagram, X (Twitter) and TikTok) proving that it is useful for evaluating if the apps include the five temporal characteristics identified: autonomy, uncertainty, eternity, expiration and fragmentation. Results confirm that the set of characteristics can be found in all the social media applications analysed showing a distinctive trend: uncertainty and autonomy have the greatest presence, and expiration the lowest.